Analyzing Trust Categories and Generating Trusted Network Path of MANET using Fuzzy Credibility Distribution Function - Bandyopadhyay, S; Karforma, S (International Journal of Computer Sciences and Engineering, 2025)
Mobile ad-hoc network (MANET) is one of the significant approaches with highly decentralized and dynamic configured architecture. For transferring packets from one node to another node in MANET security is a big challenge. Trust between two consecutive nodes is a prime important factor for secure data transmission through a trusted network path. As we all know trust of any particular node observed by other one varies with time for different constrains. Here we try to depict the variation of trust with fuzzy mathematics where trust value for each node is represented with triangular fuzzy number. Using fuzzy credibility distribution function we convert the triangular fuzzy trust value in interval based form and represent the trust variation in much more reliable format. These interval based trust values are used to generate direct, indirect trust value in interval based matrix format and from them we prepare overall communication trust matrix to generate the secure network path to send data from particular source to destination